Lumpy skin disease: A growing threat to the global livestock industry - Nanik Hidayatik; Aswin Rafif Khairullah; M. Gandul Atik Yuliani; Eka Pramyrtha Hestianah; Arindita Niatazya Novianti; Ratna Damayanti; Mirza Atikah Madarina Hisyam; Ikechukwu Benjamin Moses; Riza Zainuddin Ahmad; Bantari Wisynu Kusuma Wardhani; Syahputra Wibowo; Dea Anita Ariani Kurniasih (Open Veterinary Journal)
Lumpy Skin Disease (LSD) is an infectious disease in cattle caused by the Lumpy Skin Disease Virus (LSDV) from the Poxviridae family. Historically, LSD was first documented in Northern Rhodesia (now Zambia) in 1929 as a symptom of bug bite poisoning or hypersensitivity, described as 'pseudo-urticaria'. This disease, which causes widespread malaise and persistent weakness, is a serious, economically devastating, and reportable condition that lowers cattle output. The illness starts as a biphasic fever. After fever, emaciation, ocular discharge, and agalactia, clinical signs of a minor infection develop as one or two nodular lumps two to three days later. In particular, the skin of the muzzle, back, nostrils, legs, scrotum, eyelids, lower ears, nasal, perineum, and oral mucosa, and tail display painful, hyperemic nodular lesions. A number of diagnostic methods, such as virus isolation in cell culture, transmission electron microscopy, immunohistochemistry, direct and indirect fluorescent antibody testing, agar gel immunodiffusion, Enzyme Linked Immunosorbent Assay (ELISA), western blot, and serum neutralization test (SNT), are used to confirm the clinical diagnosis. This disease is spread by arthropods, such as flies, mosquitoes, and ticks. It is most common during the rainy season, when there is a high number of biting insects, and it declines during the dry season. Numerous significant sectors and businesses have documented the direct or indirect economic impact of LSD. Since there is now no effective antiviral medication to treat LSD, the only viable method of disease containment is vaccination. [Open Vet J 2025; 15(2.000): 541-555]